Growth and yield performance of ashwagandha (Withania somnifera) under agroforestry - THAKUR, N S; VERMA, K S; RANA, R C (The Indian Journal of Agricultural Sciences, 2014)
Investigations on effect of tree-crop combinations and nitrogen levels on growth, yield and withanolides content and yield of Withania somnifera L. Dunal were carried out during 2005-2006 and 2006-2007, in mid hills of Himachal Pradesh (India). W. somnifera was grown in association with Prunus persica (fruit), Grewia optiva, Morus alba (fodder) and Setaria sphacelata (grass). The distinctive tree-crop combinations (agroforestry systems) formed were Peach + Grewia + Setaria + W. somnifera, Peach + Morus + Setaria + W. somnifera, Peach + Setaria + W. somnifera, Grewia + Setaria + W. somnifera, Morus + Setaria + W. somnifera and W. somnifera as sole crop. Three nitrogen doses, viz. 40, 80 and 120 kg/ha were applied to W. somnifera. The plant height and leaf area of ashwagandha plants was not affected by tree-crop combinations. The nitrogen dose of 120 kg/ha resulted in maximum height (44.55 cm) and leaf area (17.76 cm2/leaf). Leaf area index was maximum (0.97) for plants grown in association with Peach+Grewia+Setaria. Belowground, aboveground and total biomass yield was not affected significantly by various tree-crop combinations. It ranged from 3.23 to 3.91, 2.30 to 2.63 and 5.53 to 6.46 q/ha, respectively. The N dose 120 kg/ha gave significantly higher below, aboveground and total biomass yield to the tune of 5.23, 3.37 and 8.60 q/ha, respectively. Withanolide content in roots varied from 0.73 to o.79 per cent but was not affected due to different tree- crop combinations and nitrogen doses.